ANALISIS PENGARUH MOTIVASI DAN KEPUASAN TERHADAP KINERJA PETERNAK AYAM BROILER POLA KEMITRAAN (CONTRACT FARMING) DI KABUPATEN KAMPAR - Dwiko Elfan Batubara; Cepriadi Cepriadi; Roza Yulida (Indonesian Journal of Agricultural Economics, 2021)
This study aims to determine the level of motivation and satisfaction to the performance of broilers involved in contract farming and to analyze the influence of motivation and satisfaction on the performance of broiler farmers in contract farming partnerships. This study uses primary and secondary data. Secondary data was obtained from the Central Bureau of Statistics and primary data was collected by questionnaire to 40 respondents using convenience sampling techniques. Then the data is analyzed qualitatively and quantitatively. The validity and reliability of the data was tested using SPSS 23. Quantitative data is the interpretation of the likert scale and the interpretation of multiple linear regressions with SPSS 23 include: coefficient of determination, test F and test T. For motivation variables obtained an average score of 3.19 which indicates that farmers feel quite motivated in collaboration with the core company. On the variable satisfaction has an average score of 3.59 indicates that the farmer is satisfied during partnering. On the performance variable the score value is 3.18 indicating that the farmer has a pretty good relationship with the company. Multiple regression results showed that the coefficient of determination (R2) was 0.648, meaning 64.8 percent of motivation and satisfaction variables significantly affected the performance of broiler chicken breeders, while the remaining 35.2 percent were influenced by other variables outside the equation model.